2016
DOI: 10.1590/s0100-736x2016001200004
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, serotyping and antimicrobial resistance pattern of Salmonella from feces and lymph nodes of pigs

Abstract: Resumo.-[Isolamento, sorotipagem e padrões de resistência a antimicrobianos de Salmonella em fezes e linfonodos de suínos.] Nas últimas décadas, o aumento de cepas circulante de Salmonella concomitantemente a resistência microbiana tem despertado a preocupação dos órgãos de Saúde Pública. Deste modo, o objetivo do presente trabalho foi pesquisar a presença de Salmonella a partir de fezes (n=50), linfonodos mediastinos (n=50), mesentéricos (n=50) e submandibular (n=50) oriundos de um abatedouro suíno. As cepas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…S. Typhimurium and its monophasic variant were the predominant serotypes and accounted for about 90% of all isolates. This finding is similar to the findings in other countries of the European Union, Brazil, China, Japan, and the United States ( 4 , 32 , 33 ). Although studies from other parts of the world also report Derby as another common serotype ( 34 ), we did not find this serotype in our study, nor did we detect S. Choleraesuis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…S. Typhimurium and its monophasic variant were the predominant serotypes and accounted for about 90% of all isolates. This finding is similar to the findings in other countries of the European Union, Brazil, China, Japan, and the United States ( 4 , 32 , 33 ). Although studies from other parts of the world also report Derby as another common serotype ( 34 ), we did not find this serotype in our study, nor did we detect S. Choleraesuis.…”
Section: Discussionsupporting
confidence: 91%
“…Of concern in our study was the high prevalence of MDR (44%) – much higher than a previous study in Colombia which reported MDR of 12% ( 11 ). MDR was significantly higher in S. Typhimurium than the other serotypes, similar to reports from Brazil and China ( 32 , 33 ). These trends could be a consequence of unregulated antimicrobial use in pig production ( 11 ), but further investigation on the levels of antimicrobial use in pig farming is needed to evaluate this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rise in prevalence of Salmonella 4, [5],12:i:-in livestock and humans also raises the question of why the serovar has recently emerged and become increasingly prevalent. Salmonella 4, [5],12:i:-has repeatedly been reported to be more highly resistant to antimicrobials relative to S. Typhimurium (6,31,32), which may provide a significant advantage to its survival in swine operations with extensive antimicrobial drug use. Likewise, S. 4, [5],12:i:-is commonly resistant to heavy metals such as zinc and copper, which can be added to livestock feeds as an alternative to antibiotics to reduce bacterial infections (16,33).…”
Section: Introductionmentioning
confidence: 99%